Effect of direct injection and pivot stiffness on the static performance parameters of tilting pad journal bearings. (July 2023) - Peixoto, Thales Freitas; Tuckmantel, Felipe Wenzel da Silva; Daniel, Gregory Bregion; Cavalca, Katia Lucchesi
This work presents a thermo-hydrodynamic model of a tilting pad journal bearing (TPJB) supported on flexible pivots and considering direct injection on the bearing gap. It initially investigates separately each effect on the static characteristics of a TPJB and after, the concomitant influence of both mechanisms on the bearing performance. The study reveals both mechanisms of direct injection and pivot deflection affect the lubricant pressure and temperature distribution. Direct injection is a local effect, mainly influencing the pressure around the injection orifice and the temperature downward it. Pivot flexibility reduces the lubricant pressure and the temperature rise, as the film thickness increases with pivot deflection. For soft pivots, direct injection may reduce even further the lubricant temperature. As the pivot stiffness reduces, the journal displacement increases, but the drag torque is reduced, indicating that bearing mechanical efficiency may be increased if the tilting pads are supported on flexible pivots, whether the journal displacement is within acceptable bounds. Each considered mechanism in a TPJB may affect its performance and should be modeled accordingly.